The choroidal osteoma with subretinal haemorrhage without choroidal neovascularisation - Gawęcki, Maciej; Adamski, Janusz; Trapkowski, Adam (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
We present the case of choroidal osteoma with subretinal haemorrhage not associated with choroidal neovascularisation. 22 years old man presented with sudden onset of metamorphopsia in the right eye. Ophthalmoscopic examination showed massive subretinal haemorrhage in the superionasal quadrant of the retina. Patient underwent full diagnosis due to suspicion of melanoma malignum choroideae: fluorescein and indocyanine angiography, ultrasonographic examination, computed tomography. On these basis diagnosis of choroidal osteoma without CNV was made. Subjective symptoms regressed after resolution of haemorrhage. There is a possibility of subretinal haemorrhage without CNV in the course of choroidal osteoma.